Photoreceptor assessment using adaptive optics in resolved central serous chorioretinopathy - Meirelles,André Luiz Braga (2017)
ABSTRACT We present a case of a patient with resolved central serous chorioretinopathy (CSC) in the left eye with persistent mild visual alterations 4 years after the resolution of the disease. Left eye exam revealed a best corrected visual acuity of 20/25 and a slight change of macular pigmentation. Optical coherence tomography revealed only minor irregularities in the topography of retinal pigment epithelium and Bruch's membrane. Adaptive optics (AO) optics demonstrated lower density, spacing, and changes in the photoreceptor mosaic pattern in the left eye than in the right eye, suggesting that CSC may cause damage to cones after clinical recovery. We conclude that AO can provide additional information to assist in the treatment and follow-up of patients with CSC or other macular pathologies.